Functional Outcomes and Complications After Salvage Total Laryngectomy for Residual, Recurrent, and Second Primary Squamous Cell Carcinoma of the Larynx and Hypopharynx: A Multicenter Retrospective Cohort Study - Meulemans, Jeroen; Demarsin, Hannelore; Debacker, Jens; Batailde, Gaël; Mennes, Tillo; Laenen, Annouschka; Goeleven, Ann; Neyt, Peter; Vanclooster, Christophe; Vauterin, Tom; Delaere, Pierre; Huvenne, Wouter; et al. (Frontiers in Oncology, 2020)
Background/purpose: We analyzed complications and functional outcomes and aimed at identifying prognostic factors for functional outcomes and complications in patients who underwent salvage total laryngectomy (STL) for residual, recurrent and second primary squamous cell carcinoma (SCC) of the larynx and hypopharynx after initial (chemo)radiation. Methods: Retrospective cohort study of patients who underwent STL in 4 major Belgian reference hospitals between 2002 and 2018. Prognostic factors for functional outcomes and complications were identified with uni- and multivariable analysis. Results: A total of 405 patients were included into final analysis. STL was performed for residual tumor (40.2%) and local recurrence (40.5%) after radiotherapy-based larynx-sparing treatment of laryngeal and hypopharyngeal SCC and for second primary laryngeal or hypopharyngeal SCC after prior irradiation for another head and neck malignancy (19.4%). Tumors were clinically staged as stage I (8.9%), II (21.2%), III (36.7%) and IV (33.2%). Postoperative complications were experienced by 34.2% of patients: postoperative haemorrhage occurred in 5.4%, wound infection in 16.2% and pharyngocutaneous fistula (PCF) in 25.5% of patients. PCF was treated conservatively in the majority of patients (87.0%), with surgical closure in the remaining cases. Mean and median hospital stay were 21.3 and 16 days respectively. Early readmission proved necessary in 15.1% of cases, most often due to late PCF development (72.2%). Patients achieved total peroral intake in 94.2% of cases. However, dysphagia was reported by 31.3% of patients during follow-up. Functional speech was reported in 86.7% of cases and was most often achieved by tracheo-oesophageal puncture (TEP) (94.1%). In a multivariable model, lower preoperative hemoglobin (<12.5g/dl) was identified as an independent prognostic factor for higher overall complication rate. Patients who developed a PCF postoperatively or were treated with surgery combined with adjuvant RT or chemoradiation (vs radiotherapy alone) for their first tumor were less likely to achieve total peroral intake. Postoperative dysphagia proved more likely in patients who developed a PCF postoperatively, and less likely in patients who underwent STL without partial pharyngectomy and in patients with myocutaneous pectoralis major (PM) flap reconstruction, compared to muscle onlay PM flap. Conclusion: Acceptable complication rates and favorable functional outcomes are reported after STL.